Translating the Subtitle of MacGyver Movie “On a Wing and a Prayer” form English into Bahasa Indonesia - Bona Paramitha Putri; Martini Martini; Witri Handayani (Politeknik Negeri Padang, 2018)
This study discusses about the complete translating process that was used to translate the subtitle of MacGyver Movie “On a Wing and a prayer” from English into Bahasa Indonesia. This movie told about how to keep survive in certain condition, and also several tips and tricks in utilizing the equipment that are found in the environment. In translating the movie, the process, the method and the procedure of translation were applied. The process of translation that was used namely analyzing, drafting, revising and finalizing. Moreover, adaptation method was used in translating the subtitle of this movie. Then, the procedures that were applied are transference, through-translation, cultural equivalent, functional equivalent, shift or transposition, compensation, modulation, reduction and expansion, and synonymy. As the result, by translating this subtitle into Bahasa Indonesia and inserted it into the movie, this subtitle can be used to help the viewers to understand the content of the movie.